Predicting unintentional weight loss in patients with gastrointestinal cancer. Issue 3 (4th March 2019) - Yoon, Saunjoo L.; Kim, Jung A; Kelly, Debra Lynch; Lyon, Debra; George, Thomas J.
Abstract: Background: Unintentional weight loss is a major problem for patients with gastrointestinal (GI) cancers because it affects treatment, survival outcomes, and quality of life. To date, little is known about the trajectory of weight loss and the relationship between baseline body mass index (BMI), location of the cancer, and outcomes. The aims of this study were to investigate patterns of weight loss over time in patients with GI cancer according to BMI groups (low, normal, and high) and location of cancer. Methods: We examined de‐identified electronic medical record data of 801 adults (>2 1 years) with GI cancer using ICD‐9 codes (150–159). Descriptive statistics and linear mixed models were used to examine unintentional weight loss over time by BMI group (low, normal, and high) and to determine the effect of primary cancer site and patient characteristics on weight loss. Results: The mean age of patients was 66.5 ± 11.9 years (21–95 years), with 58% male and 86% White. Mean weight loss over 3 years was 21.39 kg. At the first observation point, 7.8% were in the low BMI group, 30.1% were in the normal, and 62% were in the high group. At the end of observation, a majority of deaths (35.5%) occurred in the low BMI group (BMI < 20 kg/m 2 ). Significant weight loss was observed in patients with gastric ( t  = −5.11, P  < 0.001), oesophageal ( t  = −4.18, P  < 0.001), and pancreatic (35.8%, t  = −3.58, P  < 0.001) cancers. Predictors of weight change were gender ( F  = 64.93, P  < 0.001), cancer stage ( F  = 7.28, P  < 0.001), and site by days ( F  = 8.24, P  < 0.001). Weight loss rates were similar among the three BMI groups, but patterns were different based on primary cancer type as a function of days within each group. Conclusions: Weight loss in patients with GI cancers has implications for survival. Patients with upper GI cancers experienced more weight loss and decreased survival rates compared with patients with lower GI cancers. Patients with a combination of upper GI cancer (oesophagogastric or pancreatic) and low baseline BMI had the fewest survival days and worst patient outcomes. Early intervention for weight management plays a critical role for improving the health outcomes and fatality rates of these patients.